Tailoring NaVO3 as a novel stable cathode for lithium rechargeable batteries. (1st June 2019) - Chen, Long; Wu, Honglun; Wang, Huiming; Chen, Liang; Pu, Xiangjun; Chen, Zhongxue
Abstract: Vanadium-based compounds hold great promise as high capacity cathode candidate for future lithium rechargeable batteries. However, developing highly stable vanadium-based cathode materials with long cycle life remains a great challenge. Herein, we report a novel layered sodium vanadium oxide, NaVO3, as a promising cathode electrode contender. This material is capable of delivering a capacity of 224.8 mAh g −1 at the current density of 150 mA g −1, and a high rate capability of 85 mAh g −1 even at a high current density of 3 A g −1 . Moreover, outstanding capacity retention of 77% after 1000 cycles is achieved. Ex situ characterizations verify that the excellent electrochemical performance of NaVO3 is attributed to superior structural stability and electrochemical reversibility upon long-term cycling. Furthermore, the lithium ion de/intercalation mechanism for NaVO3 is also revealed involving one electron transfer reaction between V 5+ and V 4+ redox couple. Considering the low cost and material sustainability as well as the outstanding electrochemical performances, we believe that NaVO3 is a highly promising cathode material for lithium rechargeable batteries and our findings may help to pave the way for developing vanadium-based layered structure materials for high-performance alkali and alkaline-earth ion batteries.